Pendidikan Pranatal dalam Tradisi Pelet Petteng Perspektif Dhukon Kandung Di Desa Sana Daja. Pasean Pamekasan - Jannah, Faridatul; Maimun, Maimun; Juhairiyah, Juhairiyah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study examines prenatal education within the Pelet Petteng tradition from the perspective of traditional birth attendants (dukun kandungan) in Sana Daja Village, Pasean, Pamekasan. Using a descriptive qualitative approach, data were collected through in-depth interviews with key informants, direct observations, and literature studies. The findings indicate that traditional birth attendants play a crucial role in pregnancy and childbirth through rituals such as prenatal massage, prayers, and herbal remedies. The community's trust in traditional birth attendants is influenced by cultural factors, limited access to modern healthcare facilities, emotional closeness, and affordability. Despite the availability of modern healthcare services, the villagers tend to prefer traditional birth attendants due to their deep understanding of local traditions and customs. This study highlights the importance of collaboration between traditional birth attendants and medical professionals to improve maternal and child healthcare services in rural communities while preserving local traditions.